STRATEGI PERANG SEMESTA MELALUI IMPLEMENTASI SILA PANCASILA PERSATUAN INDONESIA GUNA MENCEGAH PAHAM RADIKALISME DI DAERAH ISTIMEWA YOGYAKARTA - Tonny Sumarno; Lukman Yudho Prakoso (Universitas Pertahanan Republik Indonesia (UNHAN RI), 2021)
Yogyakarta Special Region is one of the historical provinces in Indonesia. Since the Indonesian nation fought for independence until the struggle to defend independence, Yogyakarta and its people have provided the best work for the Indonesian people. The high culture which is the legacy of the ancestors is well preserved. The Special Region of Yogyakarta is also known for its polite attitude towards anyone who comes. As a student city, Yogyakarta has produced many leaders. So that it becomes a special attraction for young people in Indonesia and abroad to study in Yogyakarta, this makes the city of Yogyakarta a